Poder judiciário e razoável duração do processo: crise na efetividade da cidadania - Berardo, Maria Lúcia da Matta (2016)
This essay discusses access to justice in the construction of citizenship, its normative context and, specifically, the issues deriving from the delay in the issuance of court decisions. This essay highlights the fundamental right to the reasonable duration of the process, as well as analyses the Judiciary as the instrument of state action, and the issues associated to the duration of the process, mainly its impact in the society. To meet that goals, the author discusses possible solutions to implement such fundamental right as the materialization of the ample concept of citizenship. The first section of the essay reviews the old diagnosis that identifies the causes for the excessive Judiciary workload, and the second section discusses access to justice in the 1988 Federal Constitution as the source for such increased workload. The third section aims to present the new outline for the Judiciary, with views that go beyond Law and the new rule of judges in this context; following that the author details the measures adopted to improve the Judiciary system. The fourth section reviews data reported on the Judiciary. The last section of this essay advances proposals to improve access to Justice, including alternative dispute resolution mechanisms. Finally, the author concludes that the right set forth by article 5, LXVIII of the Federal Constitution should not correspond simply to access to courts, but to effective court decisions to the citizen that had to resort to the Judiciary Systems.